2020
DOI: 10.1088/1742-6596/1460/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Teaching mathematics using snakes and ladders game to help students understand angle measurement

Abstract: Mathematics for young learners should be taught in a fun way, using a familiar context. Incorporating games into the classroom is a way to engage students in mathematics and hence improve their learning outcomes. This article reports a qualitative study conducted to improve students’ understanding of angle measurement by implementing snakes and ladders game. A class consisted of 30 fourth-grade students at a primary school in Banda Aceh, Indonesia, participated in the study. Data on the students’ activity duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…Specifically, the NDG method was found to introduce enjoyable and meaningful learning processes that enhance the interest, engagement, and achievement of high school students in learning geometric lines in the study by Busadee and Klieosinak (2017) (e.g., using cards to learn basic geometry) and in learning geometric shapes in the study by Chung et al (2017) (using board games). (Vitoria et al, 2020) found that the understanding of primary school students about angle measurement for two-dimensional shapes is better when using the NDG approach compared to conventional teaching methods. In particular, the NDG group (learning using the 'snake and ladder' board game) showed improvement in attention, interaction, and performance throughout three learning sessions.…”
Section: Infinitymentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, the NDG method was found to introduce enjoyable and meaningful learning processes that enhance the interest, engagement, and achievement of high school students in learning geometric lines in the study by Busadee and Klieosinak (2017) (e.g., using cards to learn basic geometry) and in learning geometric shapes in the study by Chung et al (2017) (using board games). (Vitoria et al, 2020) found that the understanding of primary school students about angle measurement for two-dimensional shapes is better when using the NDG approach compared to conventional teaching methods. In particular, the NDG group (learning using the 'snake and ladder' board game) showed improvement in attention, interaction, and performance throughout three learning sessions.…”
Section: Infinitymentioning
confidence: 97%
“…Past studies have been conducted to examine the role of the NDG approach in various subjects such as English grammar (Cesur, 2019), biology (Ramly et al, 2017), chemistry (Bankole, 2018), and accounting (Jamaluddin et al, 2016), and the benefits of NDG have been confirmed in these studies. In the context of learning Mathematics, several studies have also been carried out to investigate the effectiveness of NDG in learning various topics/subtopics in Mathematics, such as algebra (Michael & Anugwo, 2016), geometric shapes (Chung et al, 2017), geometric lines (Busadee & Klieosinak, 2017), numbers (Elofsson et al, 2016;Scalise et al, 2020), and angle measurement (Vitoria et al, 2020). These studies collectively highlight the positive impact of the NDG approach on learning outcomes in Mathematics across diverse content areas.…”
Section: Infinitymentioning
confidence: 99%
“…Permainan ini dilaporkan dapat meningkatkan pengetahuan dan sikap anak terhadap pemahaman anak tentang gaya hidup sehat (Fitrizah et al, 2020;Rikawarastuti et al, 2018). Permainan ular tangga juga telah digunakan oleh studi terdahulu dalam pembelajaran matematika di sekolah dasar (Archi Maulyda et al, 2021;Surya & Puspita, 2017;Vitoria et al, 2020;Wandini et al, 2021). Pada jenjang PAUD, permainan ular tangga dilaporkan dapat meningkatkan rasa percaya diri anak (Fransisca et al, 2020) dan keterampilan matematika (Chayati et al, 2021).…”
Section: Pendahuluanunclassified
“…Pembelajaran berbasis permainan memiliki keunggulan karena membuka potensi untuk partisipasi penuh siswa dalam kegiatan dengan memicu perhatian mereka pada permainan, yang berarti mereka juga memperhatikan pelajaran [5]. Pada catatan itu, kami akan mengembangkan game edukasi melalui model permainan ular tangga yang telah banyak digunakan sebagai media pembelajaran bagi siswa, seperti pembelajaran matematika [4]. Kesederhanaan permainan membuatnya mudah untuk dimodifikasi oleh para peneliti untuk mencapai tujuan tertentu, seperti penelitian sebelumnya berupaya mengenalkan ular tangga sebagai media pengenalan penyakit TBC [3].…”
Section: Pendahuluanunclassified